2002
DOI: 10.1200/jco.20.4.1008
|View full text |Cite
|
Sign up to set email alerts
|

Communication Between Physicians and Older Women With Localized Breast Cancer: Implications for Treatment and Patient Satisfaction

Abstract: Greater patient-physician communication was associated with a sense of choice, actual treatment, and satisfaction with care. Technical information and caring components of communication impacted outcomes differently. Thus, the quality of cancer care for older breast cancer patients may be improved through interventions that improve communication within the physician-patient dyad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 36 publications
7
83
0
1
Order By: Relevance
“…1,[6][7][8][9][10][11][12][13][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The patients' expectations also depend on the type of the disease, 15,20 or the type of the malignancy. 13,15,19,25 Most of the literature data on the attitude of breast cancer patients towards being informed, and participation in treatment decision come from Canada, 15,17,18,26,32 the US, 7,10,25,[27][28][29][30][31]34 Australia, 6,9,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[6][7][8][9][10][11][12][13][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The patients' expectations also depend on the type of the disease, 15,20 or the type of the malignancy. 13,15,19,25 Most of the literature data on the attitude of breast cancer patients towards being informed, and participation in treatment decision come from Canada, 15,17,18,26,32 the US, 7,10,25,[27][28][29][30][31]34 Australia, 6,9,…”
Section: Discussionmentioning
confidence: 99%
“…In older patients, a better patientphysician communication associated with greater satisfaction with care was more often initiated by surgical oncologists and breast-specialists than by other surgeons. 30 We believe that psychooncological care, during all over the treatment process, is also of higher level in specialized breast units. 37 Among British breast cancer patients, those who were offered a choice of surgical treatment, showed less depression than those who were not.…”
mentioning
confidence: 99%
“…The same amount of information that is provided to younger patients with breast carcinoma by any given individual physician may be all that is required, which also was suggested in a study that indicated a correlation between the number of treatment options discussed and the receipt of BCS. 49 In addition, delivering age pertinent and/or ethnic group pertinent information on a personal basis, rather than relying on inanimate or other less private interpersonal sources of information, may further pave the way to optimizing the provision of information and reducing breast carcinoma treatment disparities in these vulnerable patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 In addition, outcome estimates are an important part of the initial discussion between a patient and physician regarding the relative benefit of various treatment options, and of the informed consent process. While it is possible that patients gave inflated estimates in a one-on-one interview setting or by telephone, as opposed to a more anonymous selfadministration setting, our results in this older, acutely ill population are consistent with previous studies that examined patients' estimates of the benefits of therapy and the deleterious effects that could occur from therapy.…”
Section: Discussionmentioning
confidence: 99%